Clinical summary of temporary screw combined with wire traction technique for condylar neck fracture reduction - ZHANG Haifeng; XIN Pengfei; LI Sinian; SUN Rui (Kouqiang hemian waike zazhi)
[Objective:] To investigate the application and efficacy of a temporary screw and steel wire traction technique during reduction surgery for mandibular condylar neck fractures. [Methods:] A total of eight patients with condylar neck fractures who underwent open reduction and internal fixation in our department between June 2023 and May 2024 were selected for this study. The operative time for condylar fracture reduction was recorded, and postoperative follow-up was conducted for six months to assess the recovery of mouth opening and occlusal relationships. [Results:] All patients successfully underwent surgery, with an average reduction and fixation time of 50 minutes. At the six-month follow-up, significant improvements in mouth opening and occlusal relationships were observed. [Conclusion:] The temporary screw and steel wire traction technique effectively facilitates the reduction of mandibular condylar neck fractures, and its operation is less restricted by the surgical approach for condylar fractures.